Applying a Virtual Reality Platform in Environmental Chemistry Education To Conduct a Field Trip to an Overseas Site - Fung, Fun Man; Choo, Wen Yi; Ardisara, Alvita; Zimmermann, Christoph Dominik; Watts, Simon; Koscielniak, Thierry; Blanc, Etienne; Coumoul, Xavier; Dumke, Rainer (Journal of Chemical Education, 2019)
Field trips are a common activity for instructors to engage students and give them a first-hand understanding of a subject, especially in environmental chemistry. However, the planning and execution for a field trip is logistically challenging and demanding of human and material resources. Here, we demonstrate the conduct of a virtual overseas field trip for 74 students with the use of a web-based virtual reality (VR) application. From the feedback after the virtual field trip, students reported general receptiveness toward such use of VR technology.